Identification and Analyzation of Differentially Expressed Transcription Factors in Endometriosis - Cong, Shanshan; Guo, Qiuyan; Cheng, Yan; Gao, Jianhua; Sun, Liyuan; Wang, Jing; Wu, Han; Liang, Tian; Zhang, Guangmei (Frontiers in Molecular Biosciences, 2021)
Endometriosis is interpreted as the existence of endometrium outside the uterine cavity, such as ovaries, fallopian tubes and pelvic cavity. Dysmenorrhea, abnormal menstruation, infertility, and chronic pelvic pain are the primary symptoms of endometriosis. Although there are many theories about the origin of endometriosis, the exact factor of the disease has not been confirmed. Therefore, many other mechanisms are still worth exploring. This research mainly analyzed the expression of transcription factors (TFs) in endometriosis and a total of 54 differentially expressed TFs were screened out. We performed the analysis of differentially expressed transcription factors (DETFs) in different conditions of endometriosis and the GO terms and KEGG enrichment analysis of DETFs in endometriosis. The PPI analysis was also carried out and two hub TFs and two sub-network were acquired from the PPI network. This research would contribute to explore new mechanism of endometriosis and search for effective therapeutic targets.